Mathematical Studies of non-Newtonian Blood Flow through a Patient-Specific Atherosclerotic Artery - Ikbal, Md. Asif; Mandal, Prashanta Kumar; Sarifuddin (Journal of Applied Nonlinear Dynamics, 2026)
Flow in an atherosclerotic vessel is a much-researched topic for over half a century, however very little is known while passing through a realistic vessel. A Mathematical model of blood flow through IVUS-VH (Intravascular ultrasound-virtual histology) derived patient-specific artery under stenotic condition has been developed. The flowing blood in this patient-specific arterial lumen is considered as the Generalised Newtonian fluid. The non-linear coupled governing equations of motion accompanied by appropriate choice of the initial and boundary conditions are solved numerically by MAC (Marker and Cell) method satisfying suitable stability conditions. Simulated results exhibited through their graphical representations predict the dimensionless pressure drop is less for Newtonian model than its non-Newtonian counterpart and the severity of the roughness contributes much to the number and length of the flow separation regions in an atherosclerotic vessel.